ALK Rearrangements Characterize 2 Distinct Types of Salivary Gland Carcinomas: Clinicopathologic and Molecular Analysis of 4 Cases and Literature Review. (22nd September 2021) - Agaimy, Abbas; Baněčková, Martina; Ihrler, Stephan; Mueller, Sarina K.; Franchi, Alessandro; Hartmann, Arndt; Stoehr, Robert; Skálová, Alena
Abstract : The majority of salivary gland carcinomas are characterized by recurrent gene fusions that proved highly valuable diagnostically, but only rarely of therapeutic impact. Most of these fusion-positive carcinomas belong to the low-grade or intermediate-grade biological category. To date, only 5 cases of salivary gland carcinomas carrying an oncogenic ALK fusion have been reported in 4 recent studies, but their phenotypic spectrum and their nosological classification remain uncharacterized. We herein describe in detail the clinicopathologic and molecular features of 4 ALK –fusion-positive salivary carcinomas and review previously reported cases to assess if they could be classified into a defined World Health Organization (WHO) category. Patients were 3 men and 1 woman aged from 67 to 79 years (median: 70 y). All tumors originated in the parotid gland. Their size ranged from 1.1 to 3 cm (mean, 2 cm). Three tumors were de novo high-grade salivary duct carcinomas (SDCs) and 1 was a low-grade intercalated-type intraductal carcinoma. Histologically, high-grade tumors were predominantly solid, composed of intimately admixed basal (CK5 +, androgen − ) and luminal (CK5 −, androgen + ) components. The remarkable basal component showed squamoid basophilic pattern imparting an adenosquamous-like appearance in all cases. Conventional apocrine intraductal high-grade carcinoma was noted in 1 case. Prominent intraductal growth of the solid basal component (highlighted by p63 staining) was seen in all cases. The tumor cells expressed CK7 (3/3), mammaglobin (3/3, 1 focal), GATA3 (3/3, 1 focal), variably CK5 (3/3), and focally the androgen receptor (1/3), but lacked expression of HER2/neu, SOX10, MUC4, TTF1, S100, and Napsin A. The low-grade tumor showed classic histologic and immunophenotypic features of intercalated-type noninvasive intraductal carcinoma. Molecular profiling showed rearrangements involving exon 20 of ALK in all cases, confirmed by ALK immunohistochemistry (IHC and FISH). The fusion partner was EML4 (n=2) and STRN (n=1) in high-grade tumors and EML4 in the intraductal carcinoma. Two patients with high-grade tumors developed progressive disease (1 died at 9 mo; 1 alive under palliative therapy at 5 mo). This series and a review of 5 published cases indicate that ALK rearrangements characterize 2 distinct subsets of salivary gland carcinomas in the spectrum of high-grade androgen-poor, basal-like SDC (total reported: 5 cases) and low-grade intercalated-type intraductal carcinomas (4 cases). Given the therapeutic relevance of ALK fusions, inclusion of ALK IHC in any atypical-looking or androgen-poor SDC and in high-grade adenocarcinoma-not otherwise specified is recommended. Absence of aberrant ALK expression in genetically characterized secretory (n=15) and intraductal (n=9) carcinomas lacking ALK fusions underlines the value of ALK IHC as a diagnostic screening method for identifying potential cases.